Avaliação de usabilidade: um estudo da percepção de qualidade no comércio eletrônico brasileiro - Costa, Eduardo Marques (2010)
Based on the concepts of usability as a measure of perceived quality, this descriptive study investigates, by evaluators view, the existence of usability in e-commerce sites. Usability has been proclaimed as an important tool for improving Web sites, especially for e-commerce sites, by helping to expand the business objectives allied with the large attendance of user satisfaction. Based on these concepts, this research investigates the degree of usability in e-commerce sites in Brazil. The main objective was to evaluate the usability of e-commerce sites through the frequency, impact and persistence of the recommendations of usability. The study of usability recommendations proposed by renowned authors allowed to extract 10 recommendations that, according to this researcher, showed to be the best way to contemplate the searched object. To test the hypotheses, the heuristic evaluation method proved to be a easy to apply and low cost method. The field research was to identify the frequency with which the usability recommendations occurs and to quantify the perceived difficulty due to lack of usability. It was searched 21 electronic commerce sites grouped into four main areas of activity, highlighting the sites of general retail, banks, bookstores, and airlines. The research results shows that even though the usability recommendations have been found in the sample sites, none of the sites individually shown to follow all the recommendations studied. The retail sites were those that showed more evidence of usability recommendations compared to the other surveyed sites. Regarding the impact of usability flaws, it was found that there is a greater perceived difficulty in the sites that do not clearly show the usability recommendations. It has been found the evidence in some sample sites that the usability failures could increase the errors in e-commerce sites.